THE IMPORTANCE OF DIDACTIC TASKS IN FORMING THE READING COMPREHENSION SKILLS OF PRIMARY STUDENTS - Abdizhamilova Mahfuza Makhmudovna (Scholar Express Journal, 2025)
This article describes the importance of formation by didactic assignments in the development of understanding students.
Keywords: skill and experience; text reading; reading comprehension